Genomic inference of contemporary effective population size in a large island population of collared flycatchers (Ficedula albicollis). Issue 16 (1st July 2021) - Nadachowska‐Brzyska, Krystyna; Dutoit, Ludovic; Smeds, Linnéa; Kardos, Martin; Gustafsson, Lars; Ellegren, Hans
Abstract: Due to its central importance to many aspects of evolutionary biology and population genetics, the long‐term effective population size ( N e ) has been estimated for numerous species and populations. However, estimating contemporary N e is difficult and in practice this parameter is often unknown. In principle, contemporary N e can be estimated using either analyses of temporal changes in allele frequencies, or the extent of linkage disequilibrium (LD) between unlinked markers. We applied these approaches to estimate contemporary N e of a relatively recently founded island population of collared flycatchers ( Ficedula albicollis ). We sequenced the genomes of 85 birds sampled in 1993 and 2015, and applied several temporal methods to estimate N e at a few thousand (4000–7000). The approach based on LD provided higher estimates of N e (20, 000–32, 000) and was associated with high variance, often resulting in infinite N e . We conclude that whole‐genome sequencing data offers new possibilities to estimate high (>1000) contemporary N e, but also note that such estimates remain challenging, in particular for LD‐based methods for contemporary N e estimation.